On the ranks of partitions modulo certain integers - Hong, Nankun (Nanyang Technological University, 2020)
This thesis focuses on the rank of partition functions, identities related to generating functions of ranks modulo different integers and Ramanujan's convolution sum. Most results in Chapters 2 and 4 are reproduced from [14] and [10], respectively.